Visual Impairment and Blindness in People with Intellectual Disabilities: A Systematic Review. - Kroezen, Marieke; den Akker, Natalie van; van Genderen, Maria M.; Wolkorte, Ria (Optometry & Visual Performance, 2020)
Background: Visual impairment and blindness have a major impact on people with intellectual disabilities (ID). This review aims to provide an overview of their prevalence and issues surrounding detection. Methods: A systematic review was conducted and included 16 studies published between 2002 and 2017 on the prevalence of visual impairment and blindness in people with ID. Results: Reported prevalence of visual impairment ranged from 7%-67%; prevalence of blindness ranged from 0.4%-25%. Age, the level of ID, and the presence of Down syndrome all increased the prevalence of visual impairment. Conclusions: The prevalence of visual impairment and blindness is higher in people with ID compared to the general population. Additionally, all evidence suggests that visual impairment often goes undetected in people with ID. It is therefore important that a more structural approach is adopted to detect visual impairment and blindness in all people with ID.